The effects of the inclusion of ensiled and dehydrated grape pomace in beef cattle diet: Growth performance, health, and economic viability - Molosse V.L.* (2023)
© 2023 Elsevier B.V.The present study aimed to determine whether the inclusion of 100 g/kg of grape pomace silage (GPS) and grape pomace bran (GPB) as a feed ingredient in place of wheat bran and soybean hulls would improve performance, health, fermentation parameters, and digestibility of steers in a feedlot. Thus, 24 crossbred steers (Charolais x Nellore) with an initial average body weight of 248 kg were allocated in a randomized controlled design (n = 8 steers/treatment) into three experimental groups: control group (traditional confinement diet), GPS diet (confinement diet with 100 g/kg of grape pomace silage, DM basic) and GPB group (confinement diet with 100 g/kg of grape pomace bran, DM basic). Diets did not influence dry matter intake; however, steers fed the GPB diet consumed higher starch and ether extract (EE). Steer fed the GPS diet had higher EE consumption. There was lower starch and EE digestibility with the GPS diet. The growth performance and rumen fermentation of the animals that received the GPS diet were not affected, unlike those consuming the GPB diet, which had a lower concentration of total short-chain fatty acid in the rumen. The diets influenced animal health, demonstrated by the modulation of the immune and inflammatory responses. The GPS steer showed higher lymphocyte counts but lower concentrations of ceruloplasmin, haptoglobin, and higher antioxidant capacity, represented by higher serum, hepatic, and intestinal protein thiols. GPS steers also showed decreased reactive oxygen species (in the liver and serum) and thiobarbituric acid reactive substances (in the liver). It was challenging to determine how significant the benefits of the GPB diet were on health and antioxidant capacity because these animals gained less weight. Finally, GPS improved economic viability, providing more significant revenue from feed costs, an effect not observed with GPB. We conclude that including GPS as an ingredient in steer diets can reduce feed costs and improve animal health in feedlot cattle.